2004
DOI: 10.1021/np030556a
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes and Flavonol Glycosides from Zingiber aromaticum and Their CYP3A4 and CYP2D6 Inhibitory Activities

Abstract: Three new sesquiterpenes, (2R,3S,5R)-2,3-epoxy-6,9-humuladien-5-ol-8-one (1), (2R,3R,5R)-2,3-epoxy-6,9-humuladien-5-ol-8-one (2), and (5R)-2,6,9-humulatrien-5-ol-8-one (3), and two new flavonol glycosides, kaempferol-3-O-(2,3-di-O-acetyl-alpha-l-rhamnopyranoside) (4) and kaempferol-3-O-(2,3,4-tri-O-acetyl-alpha-l-rhamnopyranoside) (5), were isolated from the EtOAc-soluble fraction of the water extract of Zingiber aromaticum, along with 13 known compounds (6-18). The structures of the isolated compounds were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…Each fraction was separated by repeated column chromatography and preparative TLC to give 16 compounds. Their structures were elucidated on the basis of spectroscopic analyses, to be a new sesquiterpene [2,9-humuladien-6-ol-8-one (1)], three known humulane-type sesquiterpenes [zerumbone, 8,10) zerumbone epoxide, 10) tricyclohumuladiol 11) ], three gingerols [(S)-6-gingerol, 12,13) (S)-8-gingerol, 13) (S)-10-gingerol 13) ], two shogaols [trans-6-shogaol, 14) trans-10-shogaol 15) ], two flavonoids [kaempferol-3-O-methyl ether, 16) kaempferol-3,4Ј-di-O-methyl ether 16) ], two acetylated flavonol glycosides 17) b-sitosterol, 18) and b-sitosterol glucoside. 19) Among the known compounds, trycyclohumuladiol (2), (S)-8-gingerol (3), (S)-10-gingerol (4), trans-10-shogaol (5), and b-sitosterol glucoside (6) were found for the first time in this plant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each fraction was separated by repeated column chromatography and preparative TLC to give 16 compounds. Their structures were elucidated on the basis of spectroscopic analyses, to be a new sesquiterpene [2,9-humuladien-6-ol-8-one (1)], three known humulane-type sesquiterpenes [zerumbone, 8,10) zerumbone epoxide, 10) tricyclohumuladiol 11) ], three gingerols [(S)-6-gingerol, 12,13) (S)-8-gingerol, 13) (S)-10-gingerol 13) ], two shogaols [trans-6-shogaol, 14) trans-10-shogaol 15) ], two flavonoids [kaempferol-3-O-methyl ether, 16) kaempferol-3,4Ј-di-O-methyl ether 16) ], two acetylated flavonol glycosides 17) b-sitosterol, 18) and b-sitosterol glucoside. 19) Among the known compounds, trycyclohumuladiol (2), (S)-8-gingerol (3), (S)-10-gingerol (4), trans-10-shogaol (5), and b-sitosterol glucoside (6) were found for the first time in this plant.…”
Section: Resultsmentioning
confidence: 99%
“…7) From the water extract of the rhizomes which is used for traditional treatment, we isolated 18 compounds including five new ones and reported their CYP3A4 and CYP2D6 inhibitory activities. 8) Because there is only little reports on the constituents of this plant, 8,9) as a continuation, we have carried out the phytochemical investigation of its MeOH extract and isolated a new sesquiterpene 1 together with 15 known compounds. In this paper, we report the isolation and structure elucidation of the new sesquiterpene and inhibitory activity of the isolated compounds on the metabolism mediated by CYP3A4 and CYP2D6.…”
mentioning
confidence: 99%
“…We found that MeOH extracts of Zingiber aromaticum (IC 50 , 102 mg/ml) and Piper cubeba (IC 50 , 53 mg/ ml) showed potent inhibitory activity against CYP3A4, while the MeOH extract of Catharanthus roseus revealed very potent inhibition against CYP2D6 with an IC 50 value of 11 mg/ml. 5) In addition, we reported the CYP3A4 and CYP2D6 inhibitory constituents of Z. aromaticum 6) and P. cubeba.…”
mentioning
confidence: 98%
“…This mean 95.4% antiradical activities of Zingiberaceae family extracts were donated by phenolic compounds and as many as 4.6% activities were donated by other compounds. Phenolic compound contained in Zingiberaceae family are gingerol, shogaol, gingeron (Ravindran, et al, 2005), bisdescurcuminoid (Wulandari, 1996), kaempferol (Usia, et al, 2004), flavonoid and non polar constituents such as curcuminoid, kavapiron and gingerol (Sirat, et al, 1996), galangin, kaempferid and pinobanksin flavononol (Hisashi, et al, 2005), 3-O-metil galangin (Tao, et al, 2006).…”
Section: Correlation Between Radical Scavenging Activity and Total Phmentioning
confidence: 99%
“…Lempuyang gajah (Zingiber littorale) repoted to have antiulcer, antioxidant, antimicrobia (Bhuiyan, et al, 2009), antitumor and antiinflamation (Murakmi, et al, 2002;Sakinah, et al, 2007;Abdul, et al, 2008). Some compounds contained in Zingiberaceae family are phenolic substances such as gingerol, shogaol, gingeron (Ravindran, et al, 2005), bidescurcuminoid (Wulandari, 1996), kaempferol (Usia, et al, 2004), flavonoid, terpenoid and non polar constituents such as curcuminoid, kava piron and gingerol (Sirat, et al, 1996). Those substances have been known to have antiradical (Sirat, et al, 1996).…”
Section: Introductionmentioning
confidence: 99%